2018
DOI: 10.1007/s11524-018-00333-1
|View full text |Cite
|
Sign up to set email alerts
|

High-Effort Coping and Cardiovascular Disease among Women: A Systematic Review of the John Henryism Hypothesis

Abstract: African-American women living in the United States experience higher cardiovascular disease risk (CVD) mortality compared to White women. Unique mechanisms, including prolonged high-effort coping in the face of discriminatory stressors might contribute to these racial disparities. The John Henryism hypothesis is a conceptual framework used to explain poor health outcomes observed among individuals with low resources who repeatedly utilize active coping to overcome barriers. The aims of our study were to summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Moreover, Subramanyam and colleagues (2013) found partial support for the JHH with hypertension among black men but not among black women. A recent systematic review of the JHH among black women also demonstrated mixed findings (Felix et al 2019). More specifically, although some studies have found support for the JHH, others have yielded results that are opposite of what the JHH posits, and some have not found an association at all (Felix et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Subramanyam and colleagues (2013) found partial support for the JHH with hypertension among black men but not among black women. A recent systematic review of the JHH among black women also demonstrated mixed findings (Felix et al 2019). More specifically, although some studies have found support for the JHH, others have yielded results that are opposite of what the JHH posits, and some have not found an association at all (Felix et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of the JHH among black women also demonstrated mixed findings (Felix et al 2019). More specifically, although some studies have found support for the JHH, others have yielded results that are opposite of what the JHH posits, and some have not found an association at all (Felix et al 2019). Given that the John Henryism construct was developed based on the experiences and characteristics of black men, most studies have focused on the ways it influences this population.…”
Section: Introductionmentioning
confidence: 99%
“…While some levels of stress are normal and easily managed, a problem ensues when stress becomes chronic, intolerable, and toxic (Franke, 2014). Failure to address and manage stress, resulted in increased problems regarding normal mental and physical functioning (Felix et al, 2018). When stress occurs, cortisol levels initially rise but then stop working when stress becomes chronic (Boyd, 2018).…”
Section: Toxic Stress and Depressionmentioning
confidence: 99%
“…In addition, the provider is always continuing to learn more about the cultural nuances of their patients/clients (Warren, 2018). Most importantly, providers need to initially examine and assess their feelings, attitudes, and responses related to cultural perspectives that are different from what they are accustomed to and thus learn to feel a level of comfortableness when encountering these differences (Felix et al, 2018;Purnell, 2019;Warren, 2015). The implications for mental health education, practice, and research are numerous.…”
Section: Racial and Ethnic Diverse Perspectivesmentioning
confidence: 99%
“…Other researchers have described this concept as "vigilance" ( Himmelstein, Young, Sanchez, & Jackson, 2015 ) with applicability to diverse racial/ethnic groups. Overall, the fi ndings on vigilant, high-eff ort coping are mixed, with evidence of limited eff ect or diff erential impact on health across populations by race, sex, and socioeconomic status ( Felix et al, 2019 ;Subramanyam et al, 2013 ).…”
Section: Racism and Stressmentioning
confidence: 99%